Assédio sexual no ambiente de trabalho - MARTINS, Ananda Sabrina dos Santos; VASCONCELOS, Emerson Ramires de; ROCHA, Marco Aurélio; PALMA, Miriane Cristine Miguel (240, 2023)
O assédio sexual no ambiente de trabalho demanda atenção sob a perspectiva dos direitos humanos e do funcionamento eficiente das organizações. O presente artigo explora a abordagem contra o assédio no local de trabalho, destacando a posição crucial do técnico de segurança do trabalho diante dessas ocorrências. A pesquisa adotou uma metodologia de revisão bibliográfica para investigar o combate ao assédio sexual no ambiente de trabalho. Os objetivos incluem a compreensão dos aspectos jurídicos, a análise dos impactos na saúde organizacional, a revisão de estratégias de prevenção e a avaliação do papel do técnico de segurança do trabalho.

Sexual harassment in the workplace demands attention from the perspective of human rights and the efficient functioning of organizations. This article explores the approach to combating harassment in the workplace, highlighting the crucial role of the occupational safety technician in addressing such occurrences. The research has adopted a methodology of literature review to investigate the combat against sexual harassment in the workplace. The objectives include understanding legal aspects, analyzing impacts on organizational health, reviewing prevention strategies, and evaluating the role of the occupational safety technician.
Sexual Harassment in the workplace
Keywords: Assédio sexual; Ambiente de trabalho; Segurança do trabalho; Segurança